2019
DOI: 10.1155/2019/5642149
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Aging Effects of Schisandrae chinensis Fructus Extract: Improvement of Insulin Sensitivity and Muscle Function in Aged Mice

Abstract: Schisandrae chinensis Fructus has a long history of medicinal use as a tonic, a sedative, and an antitussive drug. In this study, we investigated the beneficial effects of Schisandrae chinensis Fructus ethanol extract (SFe) on metabolism in an aged mouse model. Sixteen-month-old C57BL/6J mice were fed with a diet supplemented with SFe for 4 months. Insulin sensitivity was lower at 20 months of age than at 16 months of age; however, the decrease in insulin sensitivity was less in SFe-fed mice. SFe supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Previously, we found that the ethanolic extract of the Schisandra fruit significantly improved muscle strength and increased muscle mass in aged mice [27]. In addition, the extract significantly downregulated myostatin expression in muscle tissues [8,27]. However, the bioactive component of Schisandra responsible for this biological activity remains undetermined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we found that the ethanolic extract of the Schisandra fruit significantly improved muscle strength and increased muscle mass in aged mice [27]. In addition, the extract significantly downregulated myostatin expression in muscle tissues [8,27]. However, the bioactive component of Schisandra responsible for this biological activity remains undetermined.…”
Section: Discussionmentioning
confidence: 97%
“…The fruits of S. chinensis have been used in traditional medicine in Korea and China and are known to be effective in the treatment of the cardiovascular diseases, fatigue and weakness, and insomnia [17,26]. Previously, we found that the ethanolic extract of the Schisandra fruit significantly improved muscle strength and increased muscle mass in aged mice [27]. In addition, the extract significantly downregulated myostatin expression in muscle tissues [8,27].…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Relative to other muscular disorders, the regulatory mechanism of E3 ligase expression in aging muscle remains largely unknown. Transcriptional levels of MuRF1 and Atrogin-1 have been determined in aged muscle of mouse, rat, and human, [30][31][32][33][34][35][36][37][38][39][40][41][42][43] but the results obtained to date are controversial. Here, we have focused on elucidating the mechanism underlying the regulation of Atrogin-1 expression by miRNAs during the muscle aging process.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to a previous report [ 44 ], we found that the STZ_Vehicle group exhibited a decrease in average CSA of type I, IIa, and IIb fibers compared with the CON_Vehicle group in the GA muscle, and the decrease in average CSA of type II fibers (type IIa and IIb) in the STZ_Vehicle group was higher than that of type I fibers. It was previously reported that SFe increases the percentage of slow fibers and induces the expression of myosin heavy chain 1 mRNA in the TA muscle of aged mice [ 20 ]. Similarly, our data showed that the administration of SFe strongly inhibited STZ-induced degradation in GA muscle slow fibers, compared with fast fibers ( Figure 3 E).…”
Section: Discussionmentioning
confidence: 99%
“…The known pharmacological effects of SF include antioxidant, antitumor, hepatoprotective, chondroprotective, antiseptic, anti-inflammatory, antiatherosclerotic, and antidiabetic activities [ 14 , 15 , 16 , 17 ]. SF extract has beneficial effects on dexamethasone-, disuse-, and aging-induced muscle wasting [ 18 , 19 , 20 ]. However, no study has investigated the effect of SF extract on muscle wasting in type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%